Comprehensive analysis of synonymous codon usage patterns in orf3 gene of porcine epidemic diarrhea virus in China. (December 2019) - Xu, Xin; Li, Pengfei; Zhang, Yating; Wang, Xianhe; Xu, Jiaxin; Wu, Xuening; Shen, Yujiang; Guo, Dexuan; Li, Yuchang; Yao, Lili; Li, Liyang; Song, Baifen; et al.
Abstract: The ORF3 protein of porcine epidemic diarrhea virus (PEDV) is found to function as an ion channel which influences virus virulence and production. Taking consideration of the importance of PEDV orf3 gene, we have performed comprehensive analysis to investigate its synonymous codon usage patterns. In this study, the results of base composition analysis showed A/T rich and G/C poor in PEDV orf3 genes, and the most abundant base was nucleotide T. The relative synonymous codon usage value in each codon revealed that codon usage bias existed. The mean ENC value of each gene was 48.75, indicating a low codon usage bias, as well as a relatively instable change in PEDV orf3 genes. The general correlation analysis between base composition and codon usage bias indicated that mutational bias has an impact on the PEDV codon usage bias. Neutral analysis suggested that natural selection pressure takes a more important influence than mutational bias in shaping codon usage bias. Moreover, other factors including hydrophobicity and aromaticity have been also found to influence the codon usage variation among the PEDV orf3 genes. This study not only represents the most systematic analysis of codon usage patterns in PEDV orf3 genes, but also provides a basic shaping mechanism of the codon usage bias. Highlights: ORF3 genes are A/T rich and C/G poor, and codon usage bias existed. Natural selection pressure plays a more important role than mutational bias in codon usage bias. Hydrophobicity and aromaticity also influence the codon usage variation.